LOW-FLOW ANESTHESIA TECHNIQUE REDUCES EMERGENCE AGITATION IN PEDIATRIC PATIENTS UNDERWENT GENERAL ANESTHESIA - CHRISTOPHER RYALINO; TJOKORDA GDE AGUNG SENAPATHI; ADINDA PUTRA PRADHANA; ANDRIAN YADIKUSUMO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This study was designed to see the risk factors that contribute to emergence agitation (EA) and also to know the effectiveness of low-flow (LF) anesthesia technique in EA in pediatric patients. Methods: A total of 200 pediatric patients aged 6 months–6 years underwent surgery with general anesthesia were divided into two groups. The high-flow (HF) group was maintained with 5 l fresh gas flow (FGF), and the LF group was maintained with 500 ml FGF. The outcome was measured after the surgery was completed on Face, Legs, Activity, Cry, and Consolability and pediatric anesthesia emergence delirium (PAED) scores. Agitation defined in PAED score ≥10, and no agitation defined in PAED score <10. Results: EA incidence in the HF group was higher compared to the LF group (59.5 vs. 4.7%, p<0.001). HF anesthesia technique was a single risk factor for agitation event, whereas LF anesthesia may prevent EA incidence until up to 92.7%. Conclusion: LF anesthesia reduced agitation incidences. The effectiveness of LF was 92.7% in reducing the incidence of agitation. HF anesthesia was the main risk factor for agitation incidences.